Assessing Instructional Resources and Students' Self-Employment Readiness through Marketing Trade Subject in Lagos State, Nigeria - Alao, Olusegun Ezekiel; Onah, Ngozi Faith (Universitas Ahmad Dahlan, 2020)
The challenges of youth unemployment and the need for a viable vocational and entrepreneurship education necessitated the introduction of trade/entrepreneurship subjects at senior secondary schools in Nigeria. Therefore, this study aimed at assessing the availability and functionality of the recommended instructional resources and the self-employment readiness of students of Marketing Trade subject. The study answered three research questions and tested one research hypothesis. The descriptive survey research design was adopted for the study. The population for the study comprised 1367 students and teachers of Marketing Trade subject in the selected public senior secondary schools in Education District IV of Lagos State, Nigeria. The sample of the study comprised 308 students and 9 available teachers of Marketing Trade subject randomly and purposively selected respectively from the population. The research instrument used was structured questionnaire. The Cronbach Alpha correlation coefficient used to determine the internal consistency of the research instrument yielded an average index of 0.88. The research questions and hypothesis data were analysed using bar-charts, mean, standard deviation and Pearson Product Moment of Correction statistical tools as appropriate. The findings show the recommended instructional resources were not adequately available and functioning in schools, and as a result, students lacked the self-efficacy and competences for self-employment readiness as marketers and entrepreneurs. It was therefore recommended that Government and other stakeholders should collaborate to provide necessary and adequate funding and instructional resources for the effective implementation of Marketing Trade subject in Nigeria.